Assessment of Isoniazid Preventive Therapy Outcome Among People Living with HIV in a Referral Hospital, Northeast Ethiopia - Mengesha Y; Ahmed M (Dove Medical Press, 2020)
Yohannes Mengesha,1 Muhammed Ahmed2 1Department of Pharmacy, Pharmaceutics Unit, Wollo University, College of Medicine and Health Sciences, Dessie, Ethiopia; 2Dessie Referral Hospital, Dessie, EthiopiaCorrespondence: Yohannes Mengesha Email joymengesha@gmail.comBackground: Tuberculosis is said to be one of the prevalent opportunistic infections and the leading cause of death among people living with human immunodeficiency virus. Although isoniazid preventive therapy (IPT) is thought to reduce the incidence of TB in HIV patients, its implementation has faced many obstacles. This study was concerned with the assessment of the outcome of IPT among people living with HIV who were on follow-up at Dessie referral Hospital (DRH), Northeast, Ethiopia.Methods: A retrospective study of medical records of 220 patients, who were enrolled at Dessie Referral Hospital from January 10/2016 to December 11/2018, were conducted from March 23/2019 to April 6/2019. A systematic random sampling method was used to select the samples for the study, and a data abstraction format was used to capture the data. All data were entered, cleared and analyzed using SPSS version 21. Chi-square test was used to identify the association of outcome between the two IPT groups, and P-value < 0.05 was considered as statistical significance.Results: The total TB prevalence in this study was 25 (11.36%). The occurrence of TB in the IPT group was 9(4.09%) and 16 (7.27%) for the non-IPT group but not statistically significant (p=0.137). From the study, about 40.9% of patients developed opportunistic infections. Of these, 62.81% and 37.18% of opportunistic infections were developed among patients in the non-IPT and the IPT groups, respectively (p=0.002), which were statistically significant, and the IPT completion rate was 61.81%.Conclusion: Although the current study showed that the IPT had not significantly reduced the prevalence of TB between IPT and the non-IPT group, the IPT has shown to significantly reduce the prevalence of opportunistic infections.Keywords: ART patients, IPT prophylaxis, DRH, TB